Rupture of the body and rupture of the language in the novel of historical memory in Peru. Comparative study of Adiós Ayacucho by Julio Ortega and La sangre de la aurora by Claudia Salazar - Cárdenas Moreno, Mónica (2016)
Two novels which represent a part of the internal armed confl ict in Peru (1980-2000) are discussed: Adios Ayacucho (1986) by Julio Ortega and La sangre de la aurora (2013) by Claudia Salazar. Although these novels are chronologically distant, both analize language transgression as a means to represent violence in the most essential matter: the body. The comparative analysis has three objectives. First, the difference between the novel of historical memory and the novel of violence in Peru is explained; second, an understanding of both novels is proposed through two important body metaphors: the bone metaphor and the liquid metaphor. Finally, we analyze how these metaphors are created not only at the level of the signifi er but the signifi ed, that is, through the fragmentation, rupture and experimentation ofthe language and its syntax.